2015
DOI: 10.1016/j.clinph.2015.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Signal features of surface electromyography in advanced Parkinson’s disease during different settings of deep brain stimulation

Abstract: h i g h l i g h t sEfficacy of deep brain stimulation (DBS) treatment was quantified here by using surface EMG and acceleration measurements. EMG signal features differed between different DBS settings for biceps brachii muscles. EMG features pointed to previously defined optimal settings in most of patients. a b s t r a c tObjective: Electromyography (EMG) and acceleration (ACC) measurements are potential methods for quantifying efficacy of deep brain stimulation (DBS) treatment in Parkinson's disease (PD). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 31 publications
1
31
0
Order By: Relevance
“…In contrast, a separate study indicated that lowering amplitude by 50% for the hemisphere corresponding to the patients' legs that exhibited the longer step length (i.e., compared with the contralateral limb), significantly reduced the frequency and duration of freezing episodes without introducing any measurable changes in velocity, stride length, or cadence . However, these improvements in freezing of gait came at the cost of a re‐emergence of other PD motor symptoms; a finding that is commensurate with the outcomes of separate studies examining the potential benefits of lower STN‐DBS amplitude . Furthermore, reducing STN‐DBS amplitude to approximately 30% of the chronic stimulation value were shown to contribute to poorer performances during post‐urography assessments in a small group of three participants .…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…In contrast, a separate study indicated that lowering amplitude by 50% for the hemisphere corresponding to the patients' legs that exhibited the longer step length (i.e., compared with the contralateral limb), significantly reduced the frequency and duration of freezing episodes without introducing any measurable changes in velocity, stride length, or cadence . However, these improvements in freezing of gait came at the cost of a re‐emergence of other PD motor symptoms; a finding that is commensurate with the outcomes of separate studies examining the potential benefits of lower STN‐DBS amplitude . Furthermore, reducing STN‐DBS amplitude to approximately 30% of the chronic stimulation value were shown to contribute to poorer performances during post‐urography assessments in a small group of three participants .…”
Section: Discussionmentioning
confidence: 69%
“…Within the five studies, there were seven experimental conditions investigated; five of which included lowering amplitude and two of which involved increasing amplitude. In studies reporting the effects of lowering amplitude relative to the chronic stimulation value, amplitudes were typically reduced (1) by 50% for one hemisphere; (2) to approximately 80%, 70%, or 30% of the chronic stimulation values; or (3) to a level that was 0.3 V lower than chronic stimulation . In contrast, studies examining the effects of increasing amplitudes included experimental conditions that involved increasing amplitudes (1) to the highest level tolerable for each patient, or (2) to a level that was 0.3 V higher than chronic stimulation …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations